2016
DOI: 10.1007/s10616-016-9949-2
|View full text |Cite
|
Sign up to set email alerts
|

A study to identify and characterize the stem/progenitor cell in rabbit meniscus

Abstract: The repair of meniscus in the avascular zone remains a great challenge, largely owing to their limited healing capacity. Stem cells based tissue engineering provides a promising treatment option for damaged meniscus because of their multiple differentiation potential. We hypothesized that meniscusderived stromal cells (MMSCs) may be present in meniscal tissue, and if their pluripotency and character can be established, they may play a role in meniscal healing. To test our hypothesis, we isolated MMSCs, bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
2
30
0
Order By: Relevance
“…). These results were consistent with previous studies . Furthermore, MeSCs‐7d‐in the injection group enhanced more neo‐tissue formation and suppressed OA progression better, as compared to the MeSCs‐7d‐mix injection group (Figs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…). These results were consistent with previous studies . Furthermore, MeSCs‐7d‐in the injection group enhanced more neo‐tissue formation and suppressed OA progression better, as compared to the MeSCs‐7d‐mix injection group (Figs.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, our team have reported that intra‐articular injection of MeSCs enhances the regeneration of the injured meniscus and delay or reduce the progression of OA induced by meniscectomy . Huang et al also reported that MeSCs may play a greater role in repair or regeneration of meniscus. Currently, injection of MeSCs has not been used clinically.…”
Section: Discussionmentioning
confidence: 94%
“…Endogenous MPCs have similar characteristics with in vitro expanded MPCs by collagenase digestion . In spite of their outstanding proliferation, the population of progenitors harvested by collagen‐digestion were extremely low with less than 0.1%.…”
Section: Discussionmentioning
confidence: 93%
“…However, there are also drawbacks to the MSC‐based approach: MSC isolation requires an invasive biopsy, and the cell culture step required to expand populations can lead to deleterious changes in phenotype . Like MSCs, progenitor cells present in the meniscus are self‐renewing and multipotent, suggesting there is potential for meniscal repair without the need for MSC harvest and implantation …”
mentioning
confidence: 99%
“…Direct intra-synovial injections of MSCs have also been employed and meniscal regeneration and resolution of pain recorded [135,141]. MSCs sourced from a number of tissues including synovial tissues [142][143][144][145], adipose [146,147], bone marrow [45, [148][149][150]] and blood vessels [151] have been applied in a number of applications to promote meniscal repair [44-48, [152][153][154][155][156][157][158] (Table 1). Co-cultures of meniscal cells and MSCs have also been examined in meniscal repair strategies [43, 159,160].…”
Section: Use Of Mscs and Chondrocytes For Meniscal Repairmentioning
confidence: 99%